Pendidikan sejarah Islam Asia Tenggara: overview penyebaran Islam melalui Bibliometrik - Suhaimi Suhaimi; Muhammad Resqi; Ifdil Ifdil; Darmawati Darmawati; Istiqomah Istiqomah; M. Fahli Zatrahadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
This study examines the most relevant themes related to the spread of Islam through bibliometric analysis using the keyword